Parameters of innate and adaptive immune response in children with virus-induced and allergen-induced bronchial asthma phenotypes - Elena V. Prosekova; Tatiana S. Sitdikova; Maxim S. Dolgopolov; Alina I. Turyanskaya; Vitaly A. Sabynych; Natalia R. Zabelina (Бюллетень сибирской медицины, 2017)
Aim. To analyze the immune mechanisms of activation of virus-induced and allergen-induced bronchial asthma phenotypes in children.Materials and мethods. We have performed an integrated assessment of parameters of innate and acquired immunity in 98 children with bronchial asthma (BA) at the age of 3–11 years in groups with virus-induced (n = 49) and allergen-induced (n = 49) phenotypes. Bronchial asthma phenotypes were verified in accordance with PRACTALL international consensus report (2008). Study exclusion criteria were: severe course of bronchial asthma and application of immunocorrecting drugs during preceding six months. To analyze immune competent cells we used flow cytofluorometer COULTER EPICS XL by Beckman Coulter Inc. Cytokine levels were identified using immunoenzyme method and reagents by R & D Diagnostics Inc. (USA); IgE – using reagents by Alkor Bio company (Saint-Petersburg); production of cytokines – using reagents by VektorBest (Novosibirsk city). Statistical processing of data was performed by Statistica. 10 program with critical significance level p < 0,05, correlations were analyzed using Spearman rank correlation coefficient.Results. Children with bronchial asthma showed enhanced expression of T-lymphocyte activation marker HLA–DR+(р < 0,05) with reduced level of CD3+CD95+- (р < 0,01), high level of serum IgE (р < 0,01), the inverse correlation between serum levels of IFNγ and IgE (r = –0,16), IFNγ and IL-13 (r = –0,25), direct correlation between IL-17A and IgE (r = 0,48), IgE and IL-13 (r = 0,56). The children with allergeninduced BA phenotype showed low expression of CD95+ on T-lymphocyte cells, predominance of Тh-2 profile cytokines, high mitogen-induced production of IL-4 and low induction of IFNγ production. Levels of cytotoxic T-lymphocytes, natural killers, expression of activation markers and CD95+ on T-lymphocyte cells and mitogen-induced synthesis of IFNγ by cells in children with virus-induced BA phenotype were lower than the same indices in healthy children (at р < 0,05; р < 0,01; р < 0,05; р < 0,01; р < 0,01). Levels of leucocytes, neutrocytes, absolute number of T-lymphocytes, T-helpers, B-lymphocytes (р < 0,001) and Th-2 – Th-17 cytokine profile in blood serum in this group were higher than the same indices in children with allergen-induced phenotype.Conclusion. Children with virus-induced BA phenotype showed presence of immune-mediated factors predisposing them to persistent viral infections and initiation of body sensibilization with development of eosinophilic inflammation, such as impairment of cellular cytotoxicity, predominance of Th-2 – Th-17 profile cytokines, inhibition of induction of IFNγ production by blood cells. The changes of thr adaptive response system in children with activation of allergen-induced BA phenotype are characterized by enhanced proliferation, inhibition of negative regulation processes, activation of synthesis of Th2 profile cytokines, and enhanced synthesis of IgE.